Identifikasi Holding Period Bank Umum Syariah di Bursa Efek Indonesia - Ainun Azaria; Sylva Alif Rusmita (Universitas Airlangga, 2019)
This study aims to determine the effect of bid-ask spread, stock return and trading volume on the holding period of sharia commercial bank shares. This study uses a purposive sampling method, and from the specified criteria there were 3 Sharia Commercial Banks obtained, that meet the criteria and can be used as samples. The data used is in the form of daily reports obtained from the IDX website. This study uses a quantitative approach with descriptive analysis analysis techniques. The results of this study indicate that the stock holding period of Islamic Commercial Banks can be seen based on the bid-ask spread, stock return and trading volume.Keywords: Holding Period Saham, Bid-Ask Spread, Return Saham, Volume PerdaganganREFFERENCESAtkins, Allen B. dan Dyl, Edward A. 1997. Transaction costs and Holding Period for common stocks. The Journal of Finance. Vol. 3 No. 1.Arma, VisitaYales. (2013). Faktor Penentu Holding Period Saham LQ45 di Bursa Efek Indonesia. Journal of Business and Banking. Vol. 3, No. 2.Chung, S. & Wei, P. 2005. The relationship between bid-ask spreads and holding period: the case of Chinese A and B Shares. Global Finance Journal. Vol. 15 : 239-249.Hidayat, Taufik. 2011. Buku Pintar Investasi Syariah. Jakarta: PT. Transmedia.Huda, Nurul dan Mustafa Edwin Nasution. 2007. Investasi pada Pasar Modal Syariah. Jakarta: Prenada Media Grup.Husnan, Suad. 2009. Dasar - Dasar Teori Portofolio dan Analisis Sekuritas. Edisi Keempat. Yogyakarta: LPP STIM YKPN.Ratnasari, Desy dan Dewi Astuti. (2014). Pengaruh Bid-Ask Spread, Market Value, dan Variance Return Terhadap Holding Period. Jurnal Finiesta. Vol. 2, No. 1.Ryandono, Muhammad Nafikh H. 2009. Bursa Efek dan Investasi Syariah. Jakarta: Serambi.Santoso, Eko Budi. 2008. Analisis Pengaruh Transaction Cost Terhadap Holding Period Saham Biasa. Jurnal Riset Akuntansi dan Keuangan. Vol. 4, No. 2.Sugiyono. 2014. MetodePenelitianBisnis. Bandung: Alfabeta.Sutedi, Adrian. 2011. Pasar Modal Syariah: Sarana Investasi Keuangan Berdasarkan Prinsip Syariah. Jakarta: Sinar Grafika.Stoll. Hans R. 1989. Infering The Componen of The Bid-Ask Spread : Theory And Emprical Test. The Journal of Finance. Vol. 4, No. 1.Tandelilin, Eduardus. 2001. Portofolio dan InvestasiTeori dan Aplikasi. Yogyakarta :Kanisius.www.idx.co.id